Validitas Soal Higher-Order Thinking Skill Matematika Berkonteks Kebencanaan untuk Siswa Sekolah Menengah Pertama - Fahlida Harnita; Rahmah Johar; M. Hasbi; Sulastri Sulastri (Universitas Hamzanwadi, 2021)
Disaster mitigation efforts in learning mathematics need to be done to foster a disaster awareness attitude in students through higher-order thinking skills (HOTS) questions in mathematics with a disaster context. One effort that can be done is to design mathematics problems in a disaster context. This study aimed to obtain valid HOTS mathematics questions in the disaster context for junior high school students. This research is development research that is limited to the self-evaluation and expert review stages only. This study obtained 16 HOTS questions in mathematics with disaster context for junior high school students, which were valid both in terms of content and construct. The disaster context used includes drought, tsunami, earthquakes, volcanic eruptions, climate change, landslides, forest fires, and floods. The implication of this research is that valid questions can be used by teachers in the teaching and learning process in the classroom.